1999
DOI: 10.1002/lt.500050503
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after liver transplantation in patients with hepatic iron overload

Abstract: Patients with hepatic iron overload who undergo orthotopic liver transplantation (OLT) have a worse 1-year survival than those who undergo transplantation for other indications; the long-term outcome in this population is unknown. The purpose of this study is to report long-term follow-up after OLT in a cohort of patients with hepatic iron overload. Five liver transplant centers in the United States reported follow-up data on 37 patients receiving a first liver transplant who had severe hepatic iron overload i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 32 publications
(41 reference statements)
0
32
1
1
Order By: Relevance
“…This included three myocardial infarctions, one case of congestive heart failure and 1 cardiac arrest in the setting of renal failure. Cardiac complications were more common 1 year after OLT, accounting for four out of eight deaths (136). In a series of nine patients undergoing OLT for haemochromatosis, eight patients developed cardiac complications including an intraoperative pulmonary embolus in one patient, congestive heart failure in three patients and arrhythmia in four patients (136).…”
Section: Complications Post-transplantmentioning
confidence: 99%
“…This included three myocardial infarctions, one case of congestive heart failure and 1 cardiac arrest in the setting of renal failure. Cardiac complications were more common 1 year after OLT, accounting for four out of eight deaths (136). In a series of nine patients undergoing OLT for haemochromatosis, eight patients developed cardiac complications including an intraoperative pulmonary embolus in one patient, congestive heart failure in three patients and arrhythmia in four patients (136).…”
Section: Complications Post-transplantmentioning
confidence: 99%
“…Several studies have reported that post-OLT survival is worse in patients with HHC compared with those who underwent OLT for other indications. [1][2][3][4][5][6] Decreased survival in patients who underwent OLT for HHC was related to an increased number of infections and cardiac complications. In one study, reduced survival in patients who underwent OLT with iron overload was independent of HFE gene status.…”
Section: Stainable Iron Was Observed In 20 Donor Livers (12 Cases 8 mentioning
confidence: 99%
“…36 A follow-up study of the same patients that reported 5-year survival analyzed the cause of death in relation to time from OLT. 38 Sepsis was the cause of 53% of deaths within the first year post-OLT, whereas cardiac complications were responsible for 50% of deaths after 1 year. Of the 8 patients who died of sepsis within the first year after OLT, sepsis was caused by a bacterial source in 4 patients, candida in 1 patient, and unknown in 3 patients.…”
Section: Post-olt Complicationsmentioning
confidence: 99%
“…38 This included 3 myocardial infarctions, 1 case of congestive heart failure, and 1 cardiac arrest in the setting of renal failure. Separated by early (Ͻ1 year post-OLT) or late (Ͼ1 year post-OLT) deaths, cardiac complications were more common in the late group.…”
Section: Post-olt Complicationsmentioning
confidence: 99%
See 1 more Smart Citation